Effect of dredging and capping with clean soil on the mitigation of algae-induced black blooms in Lake Taihu, China: A simulation study. (15th January 2022) - Zhong, Jicheng; Chen, Chao; Yu, Juhua; Shen, Qiushi; Liu, Cheng; Fan, Chengxin
Abstract: Sediment is an important source of matter that causes blackening and odor formation in a water body. The restoration of polluted sediment can suppress algae-induced black blooms to a certain degree. In this study, we compared the control effects of sediment dredging and capping with clean soil on algae-induced black blooms in Lake Taihu using indoor simulation experiments. In addition, we explored the driving effect of temperature on algae-induced black blooms using the method of gradual warming (18, 23, and 28 °C) during the experiment. No blackening of the water body was observed in the simulation stages I (18 °C) and II (23 °C), and the blackening and odor formation occurred within 3 d when the temperature increased to 28 °C in stage III, implying that high temperature was an important driving factor for algae-induced black blooms. Dredging and capping inhibited the blackening and odor formation to some extent, and the colorimetric values in the water columns were lower in the treatment groups than in the control group. At the end of the experiment, the colorimetric values of dredging and capping treatments were 56.5% and 96.7% of the colorimetric value of the control group, respectively. The control effect of dredging on the blackening elements, i.e., Fe 2+ and S 2− and the main odor forming compounds, i.e., dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS) was observed in stage II (11–20 d) and stage III (21–27 d), respectively, and the inhibition ability of dredging to suppress algal-induced black blooms was superior than that of capping with clean soil. Highlights: Dredging and capping with clean soil are compared in terms of mitigating black blooms. High temperature (28 °C) is a key driving force behind algae-induced black blooms. Dredging reduces S content in the sediment, interstitial water, and overlying water. Dredging at reasonable depths can effectively inhibit algae-induced black blooms. Inhibition effect of dredging is better than that of capping with clean soil.